Screening fungicides and antagonistic microorganisms for control fruit spot of Citrus maxima (Burm.) Merr. cv. Tup Tim Siam pomelo - Seephueak, P.; Liamnimitr, N.; Preecha, C. (International Journal of Agricultural Technology, 2024)
The screening of fungicides and antagonistic microorganisms for their ability to control fruit spot disease caused by Fusarium oxysporum of Citrus maxima (Burm.) Merr. cv. Tup Tim Siam pomelo. The results showed that prochloraz (0.19 mg/ml), thiabendazole (0.60 mg/ml) and thiophanate-methyl (1.05 mg/ml) inhibited mycelial growth 100% and followed with propiconazole (0.25 mg/ml) and fluopyram (0.12 mg/ml) + trifloxstrobin (0.12 mg/ml) inhibited mycelial growth of 85.33 and 83.33%, respectively. The optimal doses to control the causal agent, Fusarium oxysporum was prochloraz, thiabendazole and thiophanate-ethyl which were 0.5 mg/ml for 100% mycelial growth inhibition as same as propiconazole at the rate of 1 mg/ml. Moreover, three species of antagonistic microorganisms, Paenibacillus pabuli SW01/4, Trichoderma harzianum and Bacillus amyloliquefaciens KPS46 showed inhibition of mycelial growth of Fusarium oxysporum in vitro using poisoned food technique, with inhibition rates of 52.00, 37.44 and 36.00%, respectively.